Sulfamate Esters Guide Selective Radical-Mediated Chlorination of Aliphatic C–H Bonds - Short, Melanie A. (Angew Chem Int Ed Engl, 2017)
Masked alcohols are particularly appealing as directing groups because of the ubiquity of hydroxyl groups in organic small molecules. Herein, we disclose a general strategy for aliphatic γ-C(sp(3))–H functionalization guided by a masked alcohol. Specifically, we determine that sulfamate ester-derived nitrogen-centered radicals mediate 1,6-hydrogen-atom transfer (HAT) processes to guide γ-C(sp(3))–H chlorination. This reaction proceeds through a light-initiated radical chain-propagation process and is capable of installing chlorine atoms at primary, secondary, and tertiary centers.